Serbia: Transition from abortion to contraception or not? - Rašević Mirjana (Zbornik Radova: Geografski institut "Jovan Cvijić", 2007)
At the end of demographic transition and in its post-transitional phase, according to Tice’s model, contraception has become a dominant method of birth control, while induced abortions lag behind with insignificant participation. The stated model is of general type and refers to developed countries today. It is possible that differences also exist between them, but to a small extent. However, significant and even great differences exist between Tice’s model and the relation between contraception and induced abortion in Serbia.